The Need to Develop Open Source Software Ecosystem: Library Professional’s Perspective - Kannan, S.; Aravind, S. (Journal of Information and Knowledge, 2024)
To stay ahead in the competition and to hold users to themselves, proprietary software and hardware vendors develop their closed ecosystems. Seamless interconnection of devices and easy inter-operability are thus implemented for a closed circle of users and provide a niggle free experience in using applications across devices and offer seamless data transfer across devices and applications. Microsoft, Apple, and Google are integrating this strategy on all their devices and products. It is the need of the hour, for open-source software proponents and developers to rise to the occasion to combat the monopolistic tendencies that hinder openness. Library professionals who have either adopted Open-Source Software (OSS) or information professionals who are on the verge of moving in the direction of OSS need to consider investing time, effort, and resources in developing and sustaining a counter movement with an alternate OSS ecosystem.